Fuzzy e-paraopen Sets and Maps in Fuzzy Topological Spaces - M. Sankari; C. Murugesan (Utilitas Mathematica, 2021)
This article is to study the concepts of fuzzy e-paraopen and fuzzy e-paraclosed sets in fuzzy topological spaces. Further, we extent to study few class of fuzzy maps namely fuzzy e-paracontinuous, ∗-fuzzy e-paracontinuous, fuzzy e-parairresolute, fuzzy minimal e-paracontinuous, fuzzy maximal e-paracontinuous mappings and study their properties.